Efeitos do protocolo de estressores em ratos submetidos a um regime contínuo de privação de água - Silva, Paulo Eduardo da (2015)
The Chronic Mild Stress (CMS) has been described in the literature as an experimental model of anhedonia, central symptom of depression in humans. The anhedonia has been studied in this model looking for a decrease of water with sucrose consumption in rats. This result is usually observed after the animal had been subjected to a set of stressful stimuli in a moderated and chronical way, for six weeks in average. The present study aimed to investigate the effects of the Stressors Protocol in rats subjected to a continuous water deprivation regimen. Eleven male rats of Wistar lineage were studie,. All the rats were subjected to a water deprivation schedule until reaching 85% of their ad lib weights, and they were maintained at these weights for the whole study. Thirteen water and water with sucrose consumption tests were used for all the subjects, while S7 was exposed only to the liquids consumption tests. S3 subject was submitted only to the Stressors Protocol. S5 was exposed to the same conditions of S3, except that the Stressors Protocol involved only the grouping stressor. For the other eight subjects, first they had the bar press response to the two bars modeled, using water as reinforcement. Then these eight animals were subjected to a Conc VI 5 sec VI 5 sec reinforcement, each bar being associated to water or water with sucrose reinforcements (one for each bar). After four weeks in this reinforcement schedule these animals were subjected to the Stressors Protocol for six consecutive and uninterrupted weeks in their living cages. During the protocol, four subjects (S2, S6, S8 and S10) also had their bar press responses reinforced in a Conc VI 5 sec VI 5 sec schedule (group before, during and after). The other four rats (S1, S4, S9 and S11- group before and after) were not submitted to operant sessions as long as the Stressors Protocol was available. At the end of the phase when the Stressors Protocol was available, these eight subjects were again subjected to the base line condition. The main results were: (a) a weight stability for the animals subjected to the protocol, (b) a high alternation of water and water with sucrose consumption in the tests for the only subject submitted to the tests and to the protocol, not demonstrating anhedonia, (c) a reduction in the animal s food consumption and an increase of water consumption in the living cage during the protocol for seven subjects, (d) the stressors protocol was not followed by a modification of the distribution of water and water with sucrose reinforced responses by Conc VI 5sVI5s, neither during the protocol, nor after its cessation, and (e) it seems that the reinforcement value of the liquids alternated for some subjects over major of the sessions. The role of continuous water deprivation and the measures used as anhedonia indicators are discussed